University-industry collaboration, firm performance and stakeholder theory - Imaduddin, Abidin; Anita, Abdul Rani; Mohd. Rashid, Ab. Hamid; Yuserrie, Zainuddin (Universiti Selangor (UNISEL), 2014)
From the literature study it is obvious that university-industry collaborations (UIC) is generating interest in political, economic, and academic fields. Indeed, knowledge and technology are seen as a major source of long-term economic growth and technology transfer to the firm is critical and significant for firm performance. The purpose of this paper is to improve understanding on the importance of UIC concept and how it can create value to the firm especially in improving firm performance. The UIC will consider knowledge transfer and technology transfer activities from university to firm. This paper also seeks to engage how Stakeholder Theory can answer the question; what is the relationship between UIC concept and value creation, and what responsibility does firm have to university. This paper presents literature analysis concerning this research topic and explores mean of UIC, knowledge transfer, technology transfer, firm performance and Stakeholder Theory. There is evidence to support that knowledge transfer and technology transfer activities have an impact on firm performance. Theoretically, Stakeholder Theory can explain the relationship between UIC and value creation concept, and the responsibilities a firm has to a university. This finding may pave the way for firms to collaborate with university in order to achieve high performance.